Anti-oxidation transparent high-barrier composite film, preparation device and method

By adopting a three-layer composite film design, high-barrier plastics and thermoplastic polyester materials, and enhancing interlayer adhesion through ultraviolet irradiation, the problem of easy layering and damage during use is solved, and the effect of high mechanical strength and high light transmittance is achieved.

CN119305282BActive Publication Date: 2025-03-18SICHUAN PROVINCE XINDU YONGZHI PRINTING CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411856190.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-12-17
Publication Date
2025-03-18
Estimated Expiration
2044-12-17

AI Technical Summary

Technical Problem

The existing composite films are prone to delamination and damage during use, and it is difficult to achieve high mechanical strength and high light transmittance at the same time.

Method used

A composite film design with a three-layer structure, wherein the first outer film and the second outer film are made of highly barrier plastic, the middle film is made of thermoplastic polyester material, and the interlayer bonding is enhanced by ultraviolet irradiation.

Benefits of technology

The high mechanical strength and high light transmittance of the composite film are achieved, while extending the service life of the middle layer film and improving the resistance to oxidation and corrosion resistance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119305282B_ABST
    Figure CN119305282B_ABST
Patent Text Reader

Abstract

The present invention relates to the technical field of composite film preparation, and in particular to an anti-oxidation transparent high-barrier composite film, a preparation device and a method. The composite film comprises a first outer film, a middle film and a second outer film which are arranged in sequence, wherein the thickness of the first outer film is 25 μm to 150 μm; the thickness of the middle film is 50 μm to 100 μm; the thickness of the second outer film is 50 μm to 150 μm; when the first outer film, the middle film and the second outer film are extruded from a co-extrusion die head of a casting machine, ultraviolet rays are irradiated on both sides of the middle film, and the wavelength of the ultraviolet rays is 350 nm to 380 nm, and the light intensity is 15 mw / cm 2 Up to 25mw / cm 2 The irradiation time is 2s to 8s. The anti-oxidation transparent high-barrier composite film prepared by the present invention has not only high mechanical strength but also high light transmittance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of composite film preparation, and in particular to an anti-oxidation transparent high-barrier composite film, a preparation device and a preparation method. Background Art

[0002] Composite films are formed by bonding two or more film layers of different materials together through specific process methods to improve the functionality and performance of the film.

[0003] Multilayer composite film mostly adopts dry composite method, wet composite method, extrusion composite method, hot melt composite method and co-extrusion composite method. In the co-extrusion composite method, after the original extruder is placed, the raw materials are heated, sheared and melted, and then a composite film is formed by extruding a plurality of molten raw materials together through a co-extrusion die. The co-extrusion composite film has good production efficiency and does not use solvents basically. For example, the prior application of publication number CN218366027U discloses a precision casting machine, which mainly rolls after the plurality of raw materials are melted and extruded through a co-extrusion die. But the multilayer co-extrusion composite film extruded by the above-mentioned device is mainly connected by two kinds of raw materials being mutually dissolved, and there is no obvious layered interface, and obvious layered interface appears for two kinds of raw materials with poor mutual solubility, but the cohesiveness is not strong, and it is easy to be layered and damaged during use.

[0004] Therefore, those skilled in the art are committed to developing an anti-oxidation transparent high-barrier composite film, a preparation device and a method, and the prepared anti-oxidation transparent high-barrier composite film not only has high mechanical strength but also has high light transmittance. Summary of the invention

[0005] The technical problem to be solved by the present invention is to provide an anti-oxidation transparent high-barrier composite film, a preparation device and a method. The prepared anti-oxidation transparent high-barrier composite film has not only high mechanical strength but also high light transmittance.

[0006] The technical solution of the present invention to solve the above technical problems is as follows:

[0007] An anti-oxidation transparent high-barrier composite film comprises a first outer film, a middle film and a second outer film arranged in sequence, wherein the first outer film has a thickness of 25 μm to 150 μm; the middle film has a thickness of 50 μm to 100 μm; the second outer film has a thickness of 50 μm to 150 μm;

[0008] When the first outer layer film, the middle layer film and the second outer layer film are synchronously extruded from the co-extrusion die head of the casting machine, ultraviolet rays are irradiated on both sides of the middle layer film, and the wavelength of the ultraviolet rays is 350nm to 380nm, and the light intensity is 15mw / cm 2 Up to 25mw / cm 2 , irradiation time is 2s to 8s

[0009] The first outer film (m1) is made of high barrier plastic, and the middle film (m2) and the second outer film (m3) are made of thermoplastic polyester material.

[0010] The beneficial effects of adopting the above scheme are: the first outer layer film, the middle layer film and the second outer layer film have a clear hierarchical structure, and the middle layer film has a clear interface with the first outer layer film and the second outer layer film, so that the middle layer film can be used as a skeleton film, and the first outer layer film and the second outer layer film are used as coating films. The composite film is more stable, and during the tearing process of the composite film, the first outer layer film or the second outer layer film is broken and torn first, while the middle layer is less affected. The composite film still has the usage characteristics of an ordinary film, thereby extending the service life of the middle layer film.

[0011] High barrier plastics such as PVDC and EVOH have extremely high gas and moisture barrier properties. They also have good mechanical strength and toughness. The molecular structure of these materials enables them to maintain high strength and puncture resistance even when the thickness is thin. Therefore, a thickness range of 25μm to 150μm is sufficient to provide sufficient mechanical protection while maintaining the flexibility and ductility of the material.

[0012] Thermoplastic polyesters such as PET and PEN have excellent mechanical properties, including high strength, high modulus and good impact resistance. The 50μm to 100μm thickness of the middle layer film provides it with core mechanical strength, while the 50μm to 150μm thickness of the second outer layer film synergizes with the first outer layer film to enhance the overall mechanical protection. The high crystallinity and molecular orientation of these materials enable them to exhibit lower deformation and higher tear resistance when subjected to external forces.

[0013] UV irradiation (350nm to 380nm, 15mw / cm² to 25mw / cm², 2s to 8s) can generate polar groups on the surface of the middle film through photochemical reactions without destroying the transparency of the material, thereby enhancing the adhesion between the middle film and the outer film. This enhanced adhesion helps to improve the cohesion of the overall structure, thereby improving the mechanical strength. Ultraviolet irradiation exceeding the above intensity (350nm to 380nm, 15mw / cm² to 25mw / cm², 2s to 8s) will, on the one hand, cause a decrease in light transmittance and affect product performance. In addition, after the light transmittance of the product is reduced, if it is exposed to ultraviolet light under natural conditions during use, it will increase its ability to absorb ultraviolet light and accelerate aging. Through the above means, the service life of this product under natural conditions can be extended, and the light transmittance can be maintained within the service life, further enabling a simple light transmittance test to characterize whether this product can continue to be used.

[0014] High barrier plastics and thermoplastic polyester materials themselves have good transparency. By precisely controlling the wavelength and intensity of ultraviolet radiation, the interlayer bonding can be enhanced without destroying the molecular structure of the material, thereby maintaining the overall light transmittance of the composite film.

[0015] The selected UV wavelength and intensity range can effectively promote the formation of chemical bonds without destroying the chemical structure of the material, so it will not have a negative impact on the transparency of the material. On the contrary, this treatment may help reduce the irregularities of the material surface and further improve the light transmittance. It can also make the film layer structure more closely bonded, the heat conduction is more unobstructed, and its performance can still be maintained for a long time in an environment with large changes in humidity and temperature.

[0016] The ultraviolet rays emitted by the ultraviolet irradiation component irradiate both sides of the middle layer membrane, so that polar groups are generated on both sides of the middle layer membrane. The polar groups enhance the adhesion between the middle layer membrane and the first outer layer membrane and the second outer layer membrane. At the same time, there is an obvious interface between the first outer layer membrane, the second middle layer membrane and the second outer layer membrane, which increases the mechanical strength, anti-oxidation and anti-corrosion capabilities of the composite membrane.

[0017] A preparation device for an anti-oxidation transparent high-barrier composite film, applied to the above-mentioned anti-oxidation transparent high-barrier composite film, comprising:

[0018] frame;

[0019] A single screw extruder, wherein a plurality of the single screw extruders are mounted on the frame, and a filter assembly is installed at the output end of the single screw extruder;

[0020] A co-extrusion die head, wherein the input end of the co-extrusion die head is connected to the output ends of the plurality of single-screw extruders, and the co-extrusion die head is used to merge the molten materials extruded by the respective single-screw extruders to form a composite film;

[0021] The co-extrusion die head comprises a first extrusion cavity, a second extrusion cavity and a third extrusion cavity arranged in sequence, wherein the first extrusion cavity, the second extrusion cavity and the third extrusion cavity are respectively communicated with the corresponding output end of the single screw extruder,

[0022] The first extrusion cavity, the second extrusion cavity and the third extrusion cavity are used to extrude the first outer film, the middle film and the second outer film respectively.

[0023] The air knife assembly is installed between the first extrusion cavity and the second extrusion cavity, and between the second extrusion cavity and the third extrusion cavity, and the air outlet end of the air knife assembly faces both sides of the middle layer film;

[0024] A rolling assembly, the rolling assembly is mounted on the frame and is located directly below the co-extrusion die head, and a drawing assembly and a winding assembly are also provided at the output end of the rolling assembly, and the drawing assembly and the winding assembly are both mounted on the frame;

[0025] An air knife assembly, wherein the air knife assembly is mounted on the co-extrusion die head, and an air outlet end of the air knife assembly faces the roller pressing assembly;

[0026] An ultraviolet irradiation component, wherein the ultraviolet irradiation component is mounted on the frame, and the irradiation end of the ultraviolet irradiation component faces the middle layer film extruded by the co-extrusion die head;

[0027] The ultraviolet irradiation assembly includes ultraviolet lamp beads, which are electrically connected to the control device. The ultraviolet rays emitted by the ultraviolet lamp beads are irradiated on both sides of the middle layer film. The ultraviolet lamp beads are used to emit ultraviolet rays with a wavelength of 350nm to 380nm, a light intensity of 15mw / cm² to 25mw / cm², and an irradiation time of 2s to 8s;

[0028] The frame is also equipped with an electron beam device, which is used to emit electrons with an intensity of 6fA to 10fA to both ends of the middle layer membrane.

[0029] The beneficial effects of the above scheme are as follows: each single screw extruder heats and shears the raw material to form a molten cast body, which is then extruded from the co-extrusion die head after passing through the filtering assembly, and then the multi-layer cast body is rolled into one body by the rolling assembly to form a composite film;

[0030] The air outlet of the air knife assembly faces the roller pressing assembly to prevent the newly extruded cast body from sticking and bonding through roller pressing. At the same time, the air knife assembly is used to dissipate heat for the middle layer film to prevent the middle layer film from being too hot and having high fluidity. When the roller pressing assembly is rolling, the middle layer film raw material is squeezed out, resulting in a thinner middle layer film thickness, thereby improving the uniformity of each layer of film.

[0031] The middle layer membrane has a distinct interface with the adjacent layer membrane, so that the middle layer membrane can be used as a skeleton membrane, making the composite membrane more stable. During the tearing process of the composite membrane, the outer layer membrane will be broken and torn first, while the middle layer will be less affected, thus extending the service life of the skeleton membrane;

[0032] The ultraviolet rays emitted by the ultraviolet irradiation component irradiate both sides of the middle membrane, causing polar groups to be generated on both sides of the middle membrane (polar groups mainly refer to the uneven distribution of charge in molecules, such as hydroxyl, carboxyl or amino groups), and some long chains are broken to form new chemical bonds. The polar groups enhance the adhesion between the layers of the membrane, and at the same time, there are obvious interfaces between the membranes, which increases the mechanical strength, anti-oxidation and anti-corrosion capabilities of the composite membrane;

[0033] The multi-layer composite films are connected by the mutually soluble layers formed by polar groups, and have multiple levels, and the multiple levels do not interfere with each other, thereby improving the gas barrier properties of the composite film;

[0034] Since each layer of film has different refraction angles and reflection angles, the composite film has selective projection. However, after ultraviolet irradiation or induction, nanosheet films grow on the surface of each layer of film. The nanosheet films have a high transmittance to correct the light and reduce the refractive index between each layer of film, thereby improving the overall transmittance of the composite film.

[0035] The electron beam device is used to emit electrons to the middle layer film. Electron beam irradiation can cause cross-linking between polymer chains of each layer of the film to form a three-dimensional network structure, thereby improving the mechanical strength and chemical corrosion resistance of the composite film and enhancing the adhesion between each layer of the film.

[0036] Electron beam irradiation can change the surface structure of PET film and increase its mechanical properties, such as tensile strength and tear strength, which helps to improve the mechanical stability and durability of the entire multilayer film structure. At the same time, electron beam irradiation treatment may further improve the heat resistance of PET film, so that the entire multilayer film structure can remain stable in high temperature environment;

[0037] Electron beam irradiation helps to reduce pores and defects in the composite film, improve the uniformity and consistency of the composite, and reduce the refractive index of the composite film.

[0038] Based on the above technical solution, the present invention can also be improved as follows.

[0039] Furthermore, both sides of the first extrusion cavity, both sides of the second extrusion cavity and both sides of the third extrusion cavity are provided with a first die lip and a second die lip, and the first die lip and the second die lip are connected by bolts.

[0040] The beneficial effect of adopting the above further solution is that the thickness of the extruded film can be adjusted by adjusting the gap between the first die lip and the second die lip by adjusting the bolt.

[0041] Furthermore, the single-screw extruder and the drawing assembly are electrically connected to the control device, and the control device controls the flow speed of the first outer layer film, the middle layer film and the second outer layer film by controlling the extrusion pressure of the single-screw extruder and the winding speed of the drawing assembly.

[0042] The beneficial effect of adopting the above further scheme is: the control device controls the extrusion pressure of the single-screw extruder and controls the winding speed of the drawing component, which is not only used to adjust the thickness of each layer of the film, but also makes each layer of the film have a suitable flow speed, which is beneficial to the cooling of the air knife component and the irradiation of the ultraviolet component.

[0043] Furthermore, the ultraviolet irradiation assembly includes a lamp board and the ultraviolet lamp beads, a plurality of groups of the ultraviolet lamp beads are evenly arranged longitudinally, and each of the ultraviolet lamp beads is electrically connected to the control device respectively.

[0044] The beneficial effect of adopting the above further solution is that during the flow of each layer of film at a certain speed, the number of UV lamp beads that are lit is controlled so that the UV irradiation time at each position of the middle layer of film is kept within an appropriate range.

[0045] A method for preparing an anti-oxidation transparent high-barrier composite film, applied to the above-mentioned device for preparing the anti-oxidation transparent high-barrier composite film, comprises the following steps:

[0046] S100. Mixing: The first outer layer raw material, the middle layer raw material, and the second outer layer raw material are respectively put into corresponding single screw extruders;

[0047] S200. Heating: The single screw extruder heats and extrude the raw materials of each layer into a molten state, and then conveys them to the co-extrusion die after passing through a filtering component;

[0048] S300. Extrusion: by adjusting the gap between the first die lip and the second die lip with a bolt, the first extrusion cavity is used to extrude the first outer film, the second extrusion cavity is used to extrude the middle film, and the third extrusion cavity is used to extrude the second outer film;

[0049] The control device controls the flow speed of the first outer layer film, the middle layer film and the second outer layer film by controlling the extrusion pressure of the single screw extruder and controlling the winding speed of the drawing assembly;

[0050] S400. Irradiation: The ultraviolet rays emitted by the ultraviolet irradiation component are irradiated on both sides of the middle film, the wavelength of the ultraviolet rays is 350nm to 380nm, the light intensity is 15mw / cm² to 25mw / cm², and the irradiation time is 2s to 8s. During the flow of the first outer film, the middle film and the second outer film, the control device controls the number of ultraviolet lamp beads that are lit;

[0051] S500. Blowing: cooling gas blown out from the air outlet of the air knife assembly is directed toward both sides of the middle film to cool the middle film;

[0052] S600. Cooling: When the multi-layer cast film reaches the rolling assembly, the rolling assembly rolls the multi-layer cast film into one piece and cools it, and then transports it to the drawing assembly and the winding assembly in sequence.

[0053] The beneficial effects of adopting the above further scheme are: during the preparation of the composite film, the air outlet end of the air knife assembly faces the roller pressing assembly to avoid the adhesion of the just-extruded cast body and to bond it through roller pressing;

[0054] The ultraviolet rays emitted by the ultraviolet irradiation component irradiate both sides of the middle film, so that polar groups are generated at both ends of the middle film, forming new chemical bonds. The polar groups enhance the adhesion between the layers of the film, and at the same time, there are obvious interfaces between the films, which increases the mechanical strength, chemical stability, gas barrier properties, etc. of the composite film, and also makes the composite film have stable specific functions, such as selective transmission, optical properties, etc.;

[0055] The middle layer membrane has a distinct interface with the adjacent layer membranes and has excellent oxygen and moisture barrier properties, so that the middle layer membrane can be used as a skeleton membrane, making the composite membrane more stable and extending the service life of the skeleton membrane.

[0056] Furthermore, the composite film prepared in step S600 includes a first outer film, a middle film and a second outer film, the first outer film has a thickness of 25 μm to 150 μm, the middle film has a thickness of 50 μm to 100 μm, and the second outer film has a thickness of 50 μm to 150 μm.

[0057] The beneficial effect of adopting the above further solution is: improving the mechanical properties of the composite film.

[0058] Furthermore, in step S400, the wavelength of the ultraviolet light is 350nm to 380nm, and the light intensity is 15mw / cm 2 Up to 25mw / cm 2 .

[0059] The beneficial effect of adopting the above further solution is that the appropriate ultraviolet light intensity can generate sufficient polar groups on the surface of the middle layer membrane.

[0060] Further, in step S600, the gap between the two rolling cylinders in the rolling assembly is 0.01 mm to 2 mm, and the temperature of the rolling cylinders is 10°C to 25°C.

[0061] The beneficial effect of adopting the above further solution is that the rolling drum cools the multi-layer film quickly when rolling it into one body, thereby improving the preparation efficiency of the composite film.

[0062] Furthermore, after step S600, the method further includes coating the first outer film or the second outer film with a coating, including the following steps:

[0063] S610. The cooled multilayer cast film is pulled into a vacuum chamber, and the vacuum degree of the vacuum chamber is controlled at 0.1 Pa to 1 Pa;

[0064] S620. Before the multilayer cast film is introduced into the vacuum chamber, the outer surfaces of the first outer film and the second outer film are cleaned, and then aluminum oxide is vapor-deposited on the outer surface of the first outer film or the second outer film, and the vapor deposition temperature of aluminum oxide is controlled at 1000° C. to 1500° C.;

[0065] The evaporation time is controlled at 5s to 30s, the evaporation rate is controlled at 0.1nm / s to 1nm / s, and the evaporation pressure is maintained at 0.01mbar to 0.1mbar;

[0066] S630. The surface of the aluminum oxide is then coated with a barrier coating and then dried. The barrier coating is an organic-inorganic composite containing nanoparticles. The drying temperature is 80° C. to 120° C. and the drying time is 5 min to 30 min.

[0067] The beneficial effect of adopting the above further scheme is: by coating an aluminum oxide layer on the outer surface of the first outer film or the second outer film and applying a barrier coating, the oxygen and water vapor barrier properties of the composite film are significantly improved, and it can resist corrosion from a variety of chemical substances. The combination of the aluminum oxide layer and the barrier coating improves the surface hardness of the composite film, reduces wear and scratches during transportation and use, and the aluminum oxide layer can maintain the original transparency of the composite film. BRIEF DESCRIPTION OF THE DRAWINGS

[0068] Figure 1 This is a schematic diagram of the structure of an anti-oxidation transparent high-barrier composite film according to a specific embodiment of the present invention;

[0069] Figure 2 This is a schematic structural diagram of a device for preparing an oxidation-resistant transparent high-barrier composite film according to a specific embodiment of the present invention;

[0070] Figure 3 This is a schematic diagram of the co-extrusion die structure of a specific embodiment of the present invention;

[0071] Figure 4 The figure is a schematic diagram of the structure of an ultraviolet irradiation component according to a specific embodiment of the present invention.

[0072] In the accompanying drawings, the components represented by the reference numerals are listed as follows:

[0073] m1, first outer layer film; m2, middle layer film; m3, second outer layer film; 1, frame; 2, single screw extruder; 3, filtering assembly; 4, co-extrusion die; 5, rolling assembly; 6, drawing assembly; 7, winding assembly; 8, air knife assembly; 9, ultraviolet irradiation assembly; 101, first extrusion cavity; 102, second extrusion cavity; 103, third extrusion cavity; 11, ultraviolet lamp beads. DETAILED DESCRIPTION

[0074] The principles and features of the present invention are described below in conjunction with the accompanying drawings. The examples given are only used to explain the present invention and are not used to limit the scope of the present invention.

[0075] In the description of the present invention, it is necessary to understand that the terms "center", "length", "up", "down", "front", "back", "left", "right", "vertical", "horizontal", "top", "inside", "outside", "peripheral", "circumferential" and the like indicate orientations or positional relationships based on the orientations or positional relationships shown in the accompanying drawings, and are only for the convenience of describing the present invention and simplifying the description, and do not indicate or imply that the referred system or element must have a specific orientation, be constructed and operated in a specific orientation, and therefore should not be understood as a limitation on the present invention.

[0076] In the description of the present invention, “plurality” means at least two, for example, two, three, etc., unless otherwise clearly and specifically defined.

[0077] In the present invention, unless otherwise clearly specified and limited, the terms "installed", "connected", "connected", "fixed" and the like should be understood in a broad sense, for example, it can be a fixed connection, a detachable connection, or an integral connection; it can be a mechanical connection or an electrical connection; it can be a direct connection or an indirect connection through an intermediate medium, it can be the internal connection of two elements or the interaction relationship between two elements, unless otherwise clearly defined. For ordinary technicians in this field, the specific meanings of the above terms in the present invention can be understood according to specific circumstances.

[0078] like Figure 1 As shown, an anti-oxidation transparent high-barrier composite film comprises a first outer film m1, a middle film m2 and a second outer film m3 arranged in sequence, the first outer film m1 has a thickness of 25 μm to 150 μm; the middle film m2 has a thickness of 50 μm to 100 μm; the second outer film m3 has a thickness of 50 μm to 150 μm;

[0079] When the first outer film m1, the middle film m2 and the second outer film m3 are synchronously extruded from the co-extrusion die head of the casting machine, ultraviolet rays are irradiated on both sides of the middle film m2, and the wavelength of the ultraviolet rays is 350nm to 380nm, and the light intensity is 15mw / cm 2 Up to 25mw / cm 2 , the irradiation time is 2s to 8s.

[0080] The first outer layer film m1 is made of high barrier plastic (high barrier plastics mainly include PVDC, EVOH, PVA, PA, MXD2, etc.), the middle layer film m2 and the second outer layer film m3 are made of thermoplastic polyester material (thermoplastic polyester materials mainly include PEN, PE, PET, PBT, TPEE, etc.).

[0081] like Figure 2 , Figure 3 and Figure 4As shown, a preparation device for an anti-oxidation transparent high-barrier composite film is applied to the anti-oxidation transparent high-barrier composite film as described above, comprising:

[0082] Rack 1;

[0083] Single screw extruder 2, multiple single screw extruders 2 are installed on the frame 1, and a filter assembly 3 is installed at the output end of the single screw extruder 2. In this embodiment, three single screw extruders 2 are provided.

[0084] A co-extrusion die 4, the input end of the co-extrusion die 4 is connected to the output ends of the multiple single-screw extruders 2, and the co-extrusion die 4 is used to merge the molten materials extruded by the single-screw extruders 2 to form a composite film;

[0085] The rolling assembly 5 is installed on the frame 1 and is located directly below the co-extrusion die head 4. It is used to roll the multi-layer cast body into one piece to prepare a multi-layer composite film. The output end of the rolling assembly 5 is also provided with a drawing assembly 6 and a winding assembly 7. The drawing assembly 6 and the winding assembly 7 are both installed on the frame 1. The drawing assembly 6 is used to stretch and extend the composite film, and the winding assembly 7 is used to wind up the prepared composite film for standby use.

[0086] The air knife assembly 8 is installed on the co-extrusion die 4, and the air outlet end of the air knife assembly 8 faces the roller assembly 5. The air knife assembly 8 is not only used for heat dissipation, but also for preventing the layers of the cast body from sticking together in advance, while reducing the temperature difference between the interlayer films.

[0087] The ultraviolet irradiation component 9 is installed on the frame 1 , and the irradiation end of the ultraviolet irradiation component 9 faces the middle layer film extruded by the co-extrusion die 4 .

[0088] like Figure 1 ,like Figure 2 As shown, in some embodiments, the co-extrusion die head 4 has an extrusion cavity, and the multiple extrusion cavities are independent of each other. The multiple extrusion cavities are respectively connected to the output end of the single-screw extruder 2, and an air knife assembly 8 is installed on the lower side of two adjacent extrusion cavities, and the air outlet end of the air knife assembly 8 faces both sides of the middle layer film.

[0089] Specifically, the co-extrusion die head 4 has a first extrusion cavity 101, a second extrusion cavity 102 and a third extrusion cavity 103 arranged in sequence, the first extrusion cavity 101, the second extrusion cavity 102 and the third extrusion cavity 103 are respectively communicated with the corresponding output ends of the single-screw extruder 2, an air knife assembly 8 is installed between the first extrusion cavity 101 and the second extrusion cavity 102, and between the second extrusion cavity 102 and the third extrusion cavity 103, the first extrusion cavity 101, the second extrusion cavity 102 and the third extrusion cavity 103 are respectively used to extrude the first outer layer film m1, the middle layer film m2 and the second outer layer film m3, the air outlet end of the air knife assembly 8 faces both sides of the middle layer film, both sides of the first extrusion cavity 101, both sides of the second extrusion cavity 102 and both sides of the third extrusion cavity 103 are provided with a first die lip and a second die lip, and the first die lip and the second die lip are connected by bolts.

[0090] like Figure 1 , Figure 3 As shown, in another embodiment, the ultraviolet irradiation assembly 9 includes ultraviolet lamp beads 11, and multiple ultraviolet lamp beads 11 are installed on the lamp board in two rows. The ultraviolet lamp beads 11 are electrically connected to the control device (not shown in the figure), and the ultraviolet rays emitted by the ultraviolet lamp beads 11 irradiate both sides of the middle film. Specifically, the ultraviolet irradiation assembly 9 includes a lamp board and ultraviolet lamp beads 11, and multiple groups of ultraviolet lamp beads 11 are evenly arranged longitudinally, and each ultraviolet lamp bead 11 is electrically connected to the control device.

[0091] The single-screw extruder 2 and the drawing assembly 6 are electrically connected to a control device, which controls the flow rate of the first outer layer film m1, the middle layer film m2 and the second outer layer film m3 by controlling the extrusion pressure of the single-screw extruder 2 and the winding speed of the drawing assembly 6.

[0092] In other embodiments, an electron beam device is also installed on the frame 1, and the emission end of the electron beam device is directed toward the middle film. The electron beam device is used to emit electrons with an intensity of 6fA to 10fA to both ends of the middle film m2.

[0093] The present invention also provides a method for preparing an anti-oxidation transparent high-barrier composite film, which is applied to the device for preparing the anti-oxidation transparent high-barrier composite film as described above, and comprises the following steps:

[0094] S100. Mixing: The first outer layer raw material, the middle layer raw material, and the second outer layer raw material are respectively put into the corresponding single screw extruder 2;

[0095] S200. Heating: The single screw extruder 2 heats and extrude each layer of raw material into a molten state, and then passes through the filter assembly 3 and is transported to the co-extrusion die 4;

[0096] S300. Extrusion: By adjusting the gap between the first die lip and the second die lip with a bolt, the first extrusion cavity 101 is used to extrude the first outer film m1, the second extrusion cavity 102 is used to extrude the middle film m2, and the third extrusion cavity 103 is used to extrude the second outer film m3;

[0097] The control device controls the flow speed of the first outer layer film m1, the middle layer film m2 and the second outer layer film m3 by controlling the extrusion pressure of the single screw extruder 2 and the winding speed of the drawing assembly 6;

[0098] S400. Irradiation: The ultraviolet rays emitted by the ultraviolet irradiation component 9 are irradiated on both sides of the middle film. During the flow of the first outer film m1, the middle film m2 and the second outer film m3, the control device controls the number of ultraviolet lamp beads 11 to be lit, wherein the wavelength of the ultraviolet rays is 350nm to 380nm, and the light intensity is 15mw / cm 2 Up to 25mw / cm 2 , irradiation time is 2s to 8s;

[0099] S500. Blowing: The cooling gas blown out from the outlet end of the air knife assembly 8 is directed toward both sides of the middle film to cool the middle film;

[0100] S600. Cooling: When the multilayer cast film reaches the rolling assembly 5, the rolling assembly 5 rolls the multilayer cast film into one piece and cools it, and then sequentially conveys it to the drawing assembly 6 and the winding assembly 7. The gap between the two rolling cylinders in the rolling assembly 5 is 0.01 mm to 2 mm, and the temperature of the rolling cylinder is 10° C. to 25° C.

[0101] The composite film prepared in step S600 includes a first outer film, a middle film and a second outer film, the first outer film has a thickness of 25 μm to 150 μm, the middle film has a thickness of 50 μm to 100 μm, and the second outer film has a thickness of 50 μm to 150 μm.

[0102] After step S600, the process further includes coating the first outer film or the second outer film with a coating, including the following steps:

[0103] S610. The cooled multilayer cast film is pulled into a vacuum chamber, and the vacuum degree of the vacuum chamber is controlled at 0.1 Pa to 1 Pa;

[0104] S620. Before the multilayer cast film is introduced into the vacuum chamber, the outer surfaces of the first outer film and the second outer film are cleaned, and then aluminum oxide is vapor-deposited on the outer surface of the first outer film or the second outer film, and the vapor deposition temperature of aluminum oxide is controlled at 1000° C. to 1500° C.;

[0105] The evaporation time is controlled at 5s to 30s, the evaporation rate is controlled at 0.1nm / s to 1nm / s, and the evaporation pressure is maintained at 0.01mbar to 0.1mbar;

[0106] S630. The surface of the aluminum oxide is then coated with a barrier coating and then dried. The barrier coating is an organic-inorganic composite containing nanoparticles. The drying temperature is 80° C. to 120° C. and the drying time is 5 min to 30 min.

[0107] Specifically, the barrier layer includes nano-alumina particles, polyvinylidene chloride resin, a plasticizer and a curing agent.

[0108] Embodiment 1

[0109] A method for preparing an oxidation-resistant transparent high-barrier composite film comprises the following steps:

[0110] S100. Mixing: The first outer layer raw material (EVOH or PVDC), the middle layer raw material (PE), and the second outer layer raw material (PEN or PET) are respectively put into the corresponding single screw extruder 2;

[0111] S200. Heating: After the single screw extruder 2 heats and extrude the raw materials of each layer into a molten state, the raw materials are transported to the co-extrusion die 4 after passing through the filter assembly 3. Specifically, the outlet heating temperature of EVOH or PVDC is 250°C to 265°C, the outlet heating temperature of PE is 130°C to 140°C, and the outlet heating temperature of PEN or PET is 260°C to 270°C.

[0112] S300 extrusion: co-extrusion die 4 casts a variety of raw materials in a molten state to ensure that each layer of the cast body is not bonded at the outlet during extrusion;

[0113] S400. Irradiation: The ultraviolet rays emitted by the ultraviolet irradiation component 9 are irradiated on both sides of the middle film. The wavelength of the ultraviolet rays is 365nm and the light intensity is 20mw / cm 2 When the cast body flows downward, the irradiation time is 5s.

[0114] S500. Blowing: The cooling gas blown out from the outlet end of the air knife assembly 8 is directed toward both sides of the middle layer film. When blowing, avoid excessive airflow that may break the cast body layers.

[0115] S600. Cooling: When the multilayer cast film reaches the rolling assembly 5, the rolling assembly 5 rolls the multilayer cast film into one piece and cools it, and then transports it to the drawing assembly 6 and the winding assembly 7 in sequence. The gap between the two rolling cylinders in the rolling assembly 5 is 0.3 mm, and the temperature of the rolling cylinder is 20°C.

[0116] The thickness of the first outer film (EVOH or PVDC), the middle film (PE) and the second outer film (PEN or PET) are all 100 μm.

[0117] The method further comprises applying a coating on the first outer film or the second outer film, comprising the following steps:

[0118] S610. The cooled multilayer cast film is first subjected to corona treatment and then pulled into the vacuum chamber.

[0119] S620. Aluminum oxide vapor is sprayed onto the outer surface of the first outer film or the second outer film. Specifically, an aluminum block is melted on an evaporator and evaporated to form aluminum vapor. High-purity oxygen is then introduced to react and generate aluminum oxide, which is then sprayed onto the second outer film (PEN or PET) to form an aluminum oxide coating.

[0120] S630. Apply a barrier coating on the surface of the aluminum oxide and then dry it. Specifically, after the aluminum oxide coating is formed, a barrier coating is applied on the surface of the aluminum oxide coating, and then it is heated and dried using a heating rod, and then a heat-sealing coating is applied on the surface of the barrier coating and the bottom surface of the second outer film (PEN or PET), and the heat-sealing coating is formed after drying.

[0121] Embodiment 2-6

[0122] Compared with Example 1, the only difference is that the illumination time and illumination intensity are different during the preparation of the composite film, as shown in the following table:

[0123] Composite film ingredients Light intensity Lighting time Longitudinal tensile strength Transverse tensile strength Embodiment 1 PVDC, PE, PET <![CDATA[20mw / cm 2 ]]> 5s 5.1 MPa 5.3 MPa Example 2 PVDC, PE, PET 0 0 5.07 MPa 5.27 MPa Example 3 PVDC, PE, PET <![CDATA[10mw / cm 2 ]]> 2s 5.08 MPa 5.28 MPa Example 4 PVDC, PE, PET <![CDATA[30mw / cm 2 ]]> 4s 5.09 MPa 5.29 MPa Example 5 PVDC, PE, PET <![CDATA[40mw / cm 2 ]]> 6s 5.08 MPa 5.28 MPa Example 6 PVDC, PE, PET <![CDATA[50mw / cm 2 ]]> 8s 5.08 MPa 5.28 MPa

[0124] Table 1 Mechanical strength comparison table of Example 1 and Examples 2-7

[0125] Composite film ingredients Light intensity Lighting time Light transmittance The loss rate of the composite film at 140°C Embodiment 1 PVDC, PE, PET <![CDATA[20mw / cm 2 ]]> 5s 91.1% 3.73% Example 2 PVDC, PE, PET 0 0 89.2% 3.75% Example 3 PVDC, PE, PET <![CDATA[10mw / cm 2 ]]> 2s 89.6% 3.74% Example 4 PVDC, PE, PET <![CDATA[30mw / cm 2 ]]> 4s 90.1% 3.74% Example 5 PVDC, PE, PET <![CDATA[40mw / cm 2 ]]> 6s 90.2% 3.75% Example 6 PVDC, PE, PET <![CDATA[50mw / cm 2 ]]> 8s 90.2% 3.75%

[0126] Table 2 Comparison of light transmittance and loss rate of Example 1 and Examples 2-7

[0127] According to Example 1 and Examples 2-7, in Example 1, the longitudinal and transverse tensile strengths of the composite film prepared from the first outer film (PVDC), the middle film (PE) and the second outer film (PET) are 5.1 MPa and 5.3 MPa, respectively, and the longitudinal and transverse elongations at break of the composite film are 93.8% and 85.3%, respectively;

[0128] The composite membrane forms a more solid and dense membrane network structure, and the integrity of the membrane is enhanced, making it difficult for oxygen and carbon dioxide gases to pass through the composite membrane;

[0129] Each film-forming component cannot be completely melted, the surface of the film is not smooth, has a distinct interface, has a high whiteness value, and the surface of the composite film is relatively bright and has a high light transmittance;

[0130] At the same time, at 140°C, the loss rate of the composite film is less than 3.73%.

[0131] In the description of this specification, the description with reference to the terms "one embodiment", "some embodiments", "example", "specific example", or "some examples" etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representations of the above terms do not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described may be combined in any one or more embodiments or examples in a suitable manner. In addition, those skilled in the art may combine and combine the different embodiments or examples described in this specification and the features of the different embodiments or examples, without contradiction.

[0132] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.

Claims

1. An anti-oxidation transparent high-barrier composite film, characterized in that: The invention comprises a first outer film (m1), a middle film (m2) and a second outer film (m3) which are arranged in sequence, wherein the thickness of the first outer film (m1) is 25 μm to 150 μm; the thickness of the middle film (m2) is 50 μm to 100 μm; the thickness of the second outer film (m3) is 50 μm to 150 μm; When the first outer layer film (m1), the middle layer film (m2) and the second outer layer film (m3) are synchronously extruded from the co-extrusion die head of the casting machine, ultraviolet rays are irradiated on both sides of the middle layer film (m2), and the wavelength of the ultraviolet rays is 350nm to 380nm, and the light intensity is 15mw / cm 2 Up to 25mw / cm 2 , irradiation time is 2s to 8s; The first outer film (m1) is made of high barrier plastic, and the middle film (m2) and the second outer film (m3) are made of thermoplastic polyester material.

2. A device for preparing an anti-oxidation transparent high-barrier composite film, applied to the anti-oxidation transparent high-barrier composite film as claimed in claim 1, characterized in that: include Rack(1); A single-screw extruder (2), wherein a plurality of the single-screw extruders (2) are mounted on the frame (1), and a filter assembly (3) is mounted at the output end of the single-screw extruder (2); A co-extrusion die (4), the input end of the co-extrusion die (4) being connected to the output ends of the plurality of single-screw extruders (2), the co-extrusion die (4) being used to merge the molten materials extruded by the respective single-screw extruders (2) to form a composite film; The co-extrusion die head (4) comprises a first extrusion cavity (101), a second extrusion cavity (102) and a third extrusion cavity (103) which are arranged in sequence, wherein the first extrusion cavity (101), the second extrusion cavity (102) and the third extrusion cavity (103) are respectively connected to the output ends of the corresponding single-screw extruder (2). The first extrusion cavity (101), the second extrusion cavity (102) and the third extrusion cavity (103) are used to extrude the first outer layer film (m1), the middle layer film (m2) and the second outer layer film (m3), respectively. The air knife assembly (8) is installed between the first extrusion cavity (101) and the second extrusion cavity (102), and between the second extrusion cavity (102) and the third extrusion cavity (103), and the air outlet end of the air knife assembly (8) faces both sides of the middle layer film; A rolling assembly (5), the rolling assembly (5) being mounted on the frame (1) and being located directly below the co-extrusion die head (4); a drawing assembly (6) and a winding assembly (7) being further provided at the output end of the rolling assembly (5); the drawing assembly (6) and the winding assembly (7) being both mounted on the frame (1); An air knife assembly (8), the air knife assembly (8) being mounted on the co-extrusion die head (4), with an air outlet end of the air knife assembly (8) facing the roller pressing assembly (5); an ultraviolet irradiation component (9), the ultraviolet irradiation component (9) being mounted on the frame (1), and the irradiation end of the ultraviolet irradiation component (9) being directed toward the middle layer film extruded by the co-extrusion die head (4); The ultraviolet irradiation assembly (9) comprises an ultraviolet lamp bead (11), the ultraviolet lamp bead (11) is electrically connected to the control device, and the ultraviolet light emitted by the ultraviolet lamp bead (11) irradiates both sides of the middle layer film. The ultraviolet lamp bead (11) is used to emit ultraviolet light with a wavelength of 350nm to 380nm, a light intensity of 15mw / cm² to 25mw / cm², and an irradiation time of 2s to 8s; An electron beam device is also installed on the frame (1), and the electron beam device is used to emit electrons with an intensity of 6fA to 10fA to both ends of the middle layer film (m2).

3. The device for preparing the anti-oxidation transparent high-barrier composite film according to claim 2, characterized in that: Both sides of the first extrusion cavity (101), both sides of the second extrusion cavity (102) and both sides of the third extrusion cavity (103) are provided with a first die lip and a second die lip, and the first die lip and the second die lip are connected by bolts.

4. The device for preparing the anti-oxidation transparent high-barrier composite film according to claim 2, characterized in that: The single-screw extruder (2) and the drawing assembly (6) are both electrically connected to the control device, and the control device controls the flow speed of the first outer layer film (m1), the middle layer film (m2) and the second outer layer film (m3) by controlling the extrusion pressure of the single-screw extruder (2) and the winding speed of the drawing assembly (6).

5. The device for preparing the anti-oxidation transparent high-barrier composite film according to claim 2, characterized in that: The ultraviolet irradiation assembly (9) comprises a lamp panel and ultraviolet lamp beads (11), a plurality of groups of ultraviolet lamp beads (11) are evenly arranged longitudinally, and each of the ultraviolet lamp beads (11) is electrically connected to the control device.

6. A method for preparing an anti-oxidation transparent high-barrier composite film, applied to the preparation device of the anti-oxidation transparent high-barrier composite film according to any one of claims 2 to 5, characterized in that: The following steps are involved: S100. Mixing: Putting the first outer layer raw material, the middle layer raw material, and the second outer layer raw material into the corresponding single screw extruder (2); S200. Heating: The single screw extruder (2) heats and extrude the raw materials of each layer into a molten state, and then passes through a filtering component (3) and is transported to a co-extrusion die (4); S300. Extrusion: by adjusting the gap between the first die lip and the second die lip by a bolt, the first extrusion cavity (101) is used to extrude the first outer film (m1), the second extrusion cavity (102) is used to extrude the middle film (m2), and the third extrusion cavity (103) is used to extrude the second outer film (m3); The control device controls the flow speed of the first outer layer film (m1), the middle layer film (m2) and the second outer layer film (m3) by controlling the extrusion pressure of the single screw extruder (2) and the winding speed of the drawing component (6); S400. Irradiation: The ultraviolet rays emitted by the ultraviolet irradiation component (9) are irradiated on both sides of the middle film, the wavelength of the ultraviolet rays is 350nm to 380nm, the light intensity is 15mw / cm² to 25mw / cm², and the irradiation time is 2s to 8s. During the flow of the first outer film (m1), the middle film (m2) and the second outer film (m3), the control device controls the number of ultraviolet lamp beads (11) that are lit; S500. Blowing: The cooling gas blown out from the air outlet of the air knife assembly (8) is directed toward both sides of the middle film to cool the middle film; S600. Cooling: When the multi-layer cast film reaches the rolling assembly (5), the rolling assembly (5) rolls the multi-layer cast film into one piece and cools it, and then transports it to the drawing assembly (6) and the winding assembly (7) in sequence.

7. The method for preparing the anti-oxidation transparent high-barrier composite film according to claim 6, characterized in that: The composite film prepared in step S600 includes a first outer film, a middle film and a second outer film, the first outer film has a thickness of 25 μm to 150 μm, the middle film has a thickness of 50 μm to 100 μm, and the second outer film has a thickness of 50 μm to 150 μm.

8. The method for preparing the anti-oxidation transparent high-barrier composite film according to claim 6, characterized in that: In step S600, the gap between the two rolling cylinders in the rolling assembly (5) is 0.01 mm to 2 mm, and the temperature of the rolling cylinders is 10° C. to 25° C.

9. The method for preparing the anti-oxidation transparent high-barrier composite film according to claim 6, characterized in that: After step S600, the process further includes coating the first outer film or the second outer film with a coating, including the following steps: S610. The cooled multilayer cast film is pulled into a vacuum chamber, and the vacuum degree of the vacuum chamber is controlled at 0.1 Pa to 1 Pa; S620. Before the multilayer cast film is introduced into the vacuum chamber, the outer surfaces of the first outer film and the second outer film are cleaned, and then aluminum oxide is vapor-deposited on the outer surface of the first outer film or the second outer film, and the vapor deposition temperature of aluminum oxide is controlled at 1000° C. to 1500° C.; The evaporation time is controlled at 5s to 30s, the evaporation rate is controlled at 0.1nm / s to 1nm / s, and the evaporation pressure is maintained at 0.01mbar to 0.1mbar; S630. The surface of the aluminum oxide is then coated with a barrier coating and then dried. The barrier coating is an organic-inorganic composite containing nanoparticles. The drying temperature is 80° C. to 120° C. and the drying time is 5 min to 30 min.

Citation Information

Patent Citations

  • Precise co-extrusion casting machine

    CN218366027U

  • Composite packaging film and preparation method thereof

    CN114274630A

  • Polyester film and process for producing the same

    CN1450952A